PENGARUH KECUKUPAN MODAL DAN PENYALURAN KREDIT PADA PROFITABILITAS DENGAN PEMODERASI RISIKO KREDIT - Suardita, I Wayan; Putri, I G. A. M Asri Dwija (E-Jurnal Akuntansi, 2015)
Profitability is the ratio to assess the ability of the company makes a profit in matters relating to the sale, as well as capital assets. This study aimed to determine the effect of capital adequacy ratio (CAR) and loan to deposite ratio (LDR) to profitability by NPL as a moderator variable. This research was conducted at the banks listed on the Indonesia Stock Exchange period 2011 - 2013 with a population of 36 banks. This study used a purposive sampling method and 24 companies were set up as the sample with 72 observations. This research analysis techniques using multiple linear regression analysis. The results showed that CAR and LDR positive effect on profitability. Then the ratio of NPL and NPL ratio of the interaction between CAR and the interaction between the NPL ratio of the LDR has a significant effect on profitability.
Keywords: Profitabilty, Non Performing Loans